(untitled) (Mediscope, 2025)
Background: Breast cancer is one of the most common types of cancer in the world. Collagen type XI alpha 1 (COL11A1) is an important component of collagen. It is involved in the regulation of multiple biological processes, including cell proliferation, differentiation and migration. COL11A1 is overexpressed in breast cancer and also predicts poor prognosis. In Bangladesh, this sector is still less explored and this study aims to find out the expression of the COL11A1 gene in female breast cancer patients. Objective: To determine the expression of the COL11A1 gene as a potential biomarker of breast cancer. Methods: A cross-sectional study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka in collaboration with the Institution for Population and Precision Health, the University of Chicago, USA, from July 2022 to June 2023. In this study, 34 diagnosed female breast cancer patients were selected from the Department of General Surgery, Dhaka Medical College Hospital, Dhaka by purposive sampling. After informed written consent from each participant, 0.5 cm3 normal tissue and 0.5 cm3 breast tumour tissue were collected after modified radical mastectomy (MRM) in two separate Eppendorf, which contained DNA/RNA shields as a preservative. The tissue sample was sent in a biohazard bag temperature below (-80°c) to the University of Chicago, USA on dry ice for the subsequent laboratory procedures. Data was analyzed by Statistical Package for Social Science (SPSS) version 26. Results: In this study, median and IQR values of COL11A1 gene expression were significantly higher in tumor tissue compared to normal tissue of breast 3.91 (1.95–4.34) vs 4.19 (2.56–4.81), p=0.043. The expression of the COL11A1 gene in tumor breast tissue showed a significant positive correlation with the age onset of menarche (p=0.001) and a significant negative correlation with age (p=0.023). Conclusion: This finding implies that the COL11A1 gene is a biomarker of breast cancer. It might provide better information for the diagnosis, treatment plan and prognosis of breast cancer patients, and it has a significant positive correlation with the age of onset of menarche. Mediscope 2025;12(1): 1-4